IMIGRAÇÃO, TRABALHO E PRECARIZAÇÃO: AS CONDIÇÕES DE TRABALHO DO IMIGRANTE HAITIANO NA REGIÃO METROPOLITANA DE CURITIBA A PARTIR DE 2013 - Vieira, Cainã Domit (2016)
This dissertation aims to analyze the working conditions of the Haitian immigrant in the Metropolitan Region of Curitiba. To do so, the study considers the course of the Haitian from the departure of his country of origin, the journey to Curitiba, the reason for choosing Brazil, the reality faced upon arrival, the difficulties encountered, the process of personal domination to which Is subject to the search for better living conditions and the means by which these issues result in precarious work, at which point social protection and its main forms are examined: (a) the reception of Haitian immigrants by public entities and non-governmental organizations ; (B) the Brazilian migration policy; (C) the actions of the Ministry of Labor and Social Security, in particular the regularization of the situation of immigrants to provide the insertion of Haitians in the formal labor market in Brazil and the supervision of working conditions; (D) the projects and programs developed by the State of Paraná and the Universities of Paraná in relation to the conditions of the Haitian immigrant and the fight against slave labor. It is an interdisciplinary research, with a socio-juridical approach, with a qualitative approach and application of documentary analysis and the organization of the testimonies collected in the interviews in empirical categories. The methodological procedures used are: (i) interview with Haitian immigrants, with the purpose of ascertaining the reasons for the choice of Brazil, the route to Brazil and, in particular, its working conditions; (Ii) bibliographical research, to examine the process of personal domination of Haitian immigrants as workers for the acceptance of precarious work; (Iii) documentary research, with analysis of reports of insertion of immigrants in the Brazilian labor market, of the Ministry of Labor and Employment, in particular its Observatory of International Migration, with a survey of the context and main sectors in which Haitians work in Curitiba. The temporal cut of the research starts in 2013, considering the indication of the Ministry of Labor and Social Security in the sense that Haiti became the main nationality in the Brazilian formal labor market in the aforementioned year. Finally, the spatial / territorial clipping in the Curitiba Metropolitan Region results from the highlight of the Municipality as the principal in admitting workers in January 2016 (OBMIGRA).